The Implementation of Data Interoperability Services in the Government of West Sumatra Province - Hapsari, Aprilia; Permana, Iip (The Future of Education Journal, 2025)
This study aims to describe the implementation of data interoperability services within the Provincial Government of West Sumatra and to analyze the efforts made to overcome various technical challenges. The background of this research is rooted in the need for integrated, efficient, and transparent public services, which are often hindered by fragmented data systems (data silos) across government agencies. As part of the implementation of the Electronic-Based Government System (SPBE) and the One Data Indonesia (SDI) policy, the government introduced the Government Service Connectivity System (SPLP) as a means to promote data interoperability. This study employs a qualitative descriptive approach, with data collected through in-depth interviews with the West Sumatra Provincial Office of Communication and Informatics (Diskominfo) and document analysis. The findings reveal that although SPLP has been introduced as a core digital infrastructure, its implementation still faces several obstacles, including limited technical capacity of human resources, the lack of consistent data exchange standards, low inter-agency commitment, and suboptimal utilization of the SPLP. To address these issues, the West Sumatra Provincial Government has undertaken strategic measures such as conducting workshops, providing technical guidance, developing data governance regulations, and strengthening coordination among regional government organizations (OPD). The study concludes that the success of data interoperability services depends on technological readiness, strong institutional collaboration, adequate regulatory support, and continuous capacity building. By optimizing the use of SPLP and applying SPBE principles, local governments can enhance the quality of digital and sustainable public services.